Supply chain decisions under asymmetric information with cost and fairness concern. Issue 10 (26th November 2019) - Qin, Yanhong; Shao, Yunfei
ABSTRACT: The two-echelon supply chain including single supplier and single retailer is set, and we study the compact of asymmetric information on the decisions in the supply chain when the both supplier's private cost information and retailer's private fairness-concern information are asymmetry between the supply chain members, so as to study the effect of misreporting behavior and fairness concern on the supply chain. By mathematical model derivation and numerical analysis, we prove that the misreporting behavior of supplier will intensify the unfair distribution of supply chain and thus make the supply chain operation further deviate from the optimal condition.